Determining Behavior to Uptake and Its Predictors toward Cervical Cancer Screening among Women: A Case-Control Multistage Study - Eko Winarti; Dhita Kris Prasetyanti; Moh Alimansur; Rozzana Mohd Said (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Cervical cancer is a primary cause of mortality cancer among Indonesian women. Notwithstanding these threats, cervical cancer screening services have low uptake. Additionally, there was a lack of multistage case-control studies regarding positive behavior and its determinants for cervical cancer screening.